Impact of Self-Leadership Competencies on Small and Medium-Sized Enterprises in Kenya During the COVID-19 Pandemic - Waweru, Jayne Wairimu (International Leadership Journal, 2021)
Since the first COVID-19 case was identified in Kenya, the challenges it brought to small and medium-sized enterprises (SMEs) have occupied the same prominence as challenges in health. The containment measures put in place by government to manage the pandemic have affected SMEs in multiple ways, including changing consumption patterns, downsizing of staff and operations, changing business lines, and even closure. This article summarizes the results of a study that investigated the impact of self-leadership competencies on SMEs in Kenya during the COVID-19 pandemic. Specifically, the study investigated the self-leadership competencies adopted by SME leaders to cope with the challenges of COVID-19. The study was anchored on the situational theory of leadership. It used a qualitative approach to collect data from SME leaders during three focus group discussions. The results indicated that business leaders who practiced various self leadership approaches were able to adjust their work practices and sustain their enterprises.
Journal Article
Keywords: COVID-19; Kenya; Self-leadership; Self-leadership competencies; SMEs